Impact of feed intake during late gestation on piglet birth weight and reproductive performance: a dose-response study performed in gilts - Mallmann, André L (J Anim Sci, 2019)
The effects of increasing feed intake (1.8, 2.3, 2.8, and 3.3 kg/d) during late gestation of gilts on piglet birth weight and female reproductive performance were evaluated. A total of 977 gilts were fed a diet based on corn-soybean meal (3.29 Mcal ME per kg and 0.64% standardized ileal digestible lysine) from day 90 of gestation until farrowing. Gilts were weighed on days 90 and 112 of gestation, at farrowing and weaning. Born alive and stillborn piglets were weighed within 12 h of birth. Colostrum yield (CY), lactation feed intake, and litter growth rate were measured in a randomly selected subsample of 245 gilts. The data were analyzed using generalized linear mixed models. As expected, gains in body weight (BW) were different at day 112 (P < 0.001) with the greatest values observed in the 3.3 kg/d treatment. As feed intake increased during late gestation, BW, body condition score (BCS), backfat (BF), and Caliper unit also increased between day 112 and weaning (P < 0.001). No differences were found among treatments in total number of piglets born, mummified fetuses, sum of born alive and stillborn piglets, and within-litter birth weight CV (P > 0.05). Tendencies for quadratic effect of feed intake were observed for born alive piglets (P = 0.079), average birth weight of piglets (P = 0.083), and litter weight (P = 0.059). Gilts with lower feed intake during late gestation had reduced percentages of stillborn piglets than gilts with greater feed intakes. The CY decreased linearly (P < 0.05) as the feed intake was increased. No differences among treatments were found at weaning in individual piglet weight and litter weight, as well as in percentage of weaned piglets (P > 0.05). Lactation feed intake decreased as gestation feeding level increased (P < 0.05). No differences in the subsequent cycle were observed among treatments for farrowing rate, retention rate up to the next farrowing, number of total piglets born, born alive, stillborn piglets, and mummified fetuses (P > 0.05). In conclusion, increased feed intake from day 90 of gestation until farrowing resulted in increased maternal BW gain and stillborn rate, but reduced CY and lactation feed intake. A slight increase in birth weight was observed for the 2.3 kg/d treatment. Furthermore, litter growth and subsequent female reproductive performance were not affected by feed intake during late gestation.